(untitled) (International Conference on Computers in Education, 2020)
The outbreak of Covid-19 pandemic in China has suddenly changed the high school English language teaching and learning in less-developed regions, transforming offline classroom learning into online home-based learning. The changes of learning environments and learning methods brought new challenges to students’ English language learning. It’s believed that learners’ conceptions of learning had influences on their learning process and learning outcomes. In this case, the current research aimed to explore high school students’ conceptions of learning English online in the less-developed region through a large-scale questionnaire investigation. The participants were 209 twelfth grade students from Changshun Senior High School of Nationalities in Guizhou province, China. Both quantitative and qualitative data were collected based on the conceptions of learning English online (COLE) questionnaire. First, exploratory factor analysis and Cronbach’s alpha test were conducted to examine the validity and reliability of the questionnaire, and further confirmed the factorial structures of high school students’ conceptions of learning English online in the less-developed region. Then, students’ subjective responses to the open-ended question were coded and analyzed. Four major factors affecting students’ conceptions of learning English were identified, namely learning experience, discipline-based learning content, classroom teaching, and school culture. The qualitative results provided positive implications for guiding high school students to establish appropriate conceptions of learning English. It’s advised that English instructors should choose suitable teaching materials with appropriate difficulty and interesting content to stimulate students’ interest in learning English. Besides, it’s very important that English teachers should pay attention to their professional skills training and development and establish appropriate conceptions of learning English first. Finally, a good learning environment with pleasant and atmosphere and rich opportunities to communicate is needed to help guide students’ to develop sophisticated conceptions of learning English.